PENGARUH KONSENTRASI MALTODEKSTRIN PADA ADONAN BEKU TINGGI PROTEIN TERHADAP KARAKTERISTIK ROTI - Desiana Nuriza Putri; Okta Pringga Pakpahan; Damat Damat; Ari Rizki Yuspita Ningrum; Erika Novena Santoso (Jurnal Teknologi dan Industri Pangan, 2021)
The maltodextrin in frozen dough functions as the cryoprotectant to keep the structure of dough and yeast viability during freezing. This study investigated the optimum maltodextrin concentration in the high-protein frozen dough to obtain the best characteristics of sweet bread. The experimental design was a simple, completely randomized design (CRD) with one factor, i.e., maltodextrin concentrations of 0, 1, and 2% w/w. The experiment was done in triplicates with 0% maltodextrin as the control. During ten days of frozen storage, it was found that the addition of maltodextrin significantly affected the number of viable yeast after freezing. Furthermore, the addition of 2% maltodextrin produces the best bread characteristics. Furthermore, the addition of maltodextrin to the frozen dough also protects the water content during proofing which was shown by loaf volume 85.80% and water content of 15.30%. Furthermore, yeast viability and the gluten content in bread profoundly impacted the optimum elasticity crumb firmness value 2.00 N/mm².